Exploitation of Lagoon Water Bodies and Conflicts of Use: the Case of The Lagoons of Grand-Lahou (Cote D’ivoire) - ALLA, Kouadio Augustin (International Journal of Scientific Research and Management (IJSRM), 2021)
Demographic pressure, the reduction of arable land and the instability of income generated by export crops have forced the people of Grand-Lahou to show more interest in fishing activities. Thus, the exploitation of water bodies is an important strategic and economic issue for the neighbouring populations. However, in recent years, this exploitation of aquatic resources has led to conflicts between operators. The aim of this article is to analyse the procedures for resolving these conflicts and to assess their effectiveness. The methodological approach has integrated field observations and analyses carried out on the basis of information collected through interviews with stakeholders. The results reveal various forms of conflict resolution with relative levels of effectiveness. This situation is a hindrance to the efficient use of Ivorian aquatic areas. It is therefore desirable for the State to play its role by proposing more effective ways of managing these conflicts.